Peningkatkan Kemampuan Dalam Penyusunan Rkjm Bagi Kepala Sekolah SD Gugus VII Durma Uptd Jebres Surakarta Tahun 2011/2012 Melalui Supervisi Manajerial - Tri Hartanti (Universitas Muhammadiyah Surakarta, 2016)
The research is aimed to: 1) describe the managerial supervision to improve the principals’ ability in constructing the RKJM; and 2) to improve the principals’ ability in constructing the RKJM for the principals at Gugus VII Durma UPTD Dikpora Kecamatan Jebres of Surakarta through the managerial supervision using group method. The research is an Action Research. The research was done at Gugus VII Durma UPTD Dikpora Kecamatan Jebres of Surakarta. The subject of the research were 5 principals. The data collecting method were done using document and observation techniques. The data analysis was done using path model of Kemmis and Taggart.The research concludes that: 1) the managerial supervision to improve the principals’ ability in constructing the RKJM was done as follows: (a) the planning was done in refer to the problems identification; (b) the supervisor and the principals agree the supervision schedule; (c) the supervisor provided the supervision materials in the form of office conference; (d) the supervisor asked the principals to correct the RKJM they made at the end of the sessions; and (e) the supervisor provided training in the indicators that are not mastered by the principals; and 2) the managerial supervision group method is effective in improving the principals’ ability in constructing the RKJM. It is demonstrated with the principals ability impovement in each cycles.